The Effectiveness of Education on Knowledge and Attitudes About HIV/AIDS Through Leaflets and Videos on Students at SMAN 1 Tarumajaya Bekasi - Indah Yuliani; Nanda Virgita; Nurul Hidayah; Putri Ridhotun Nabila; Nanda Rizka Salsabila; Hasipah Nurseha; Inda Panti Nalova; Winarti Mutiara Sitohang (Jurnal Ners, 2026)
HIV/AIDS cases remain a global health issue, including in Indonesia. Adolescents are a group that is vulnerable to HIV/AIDS transmission due to a lack of knowledge and inappropriate attitudes towards risky behavior and people living with HIV/AIDS. Based on observations at SMAN 1 Tarumajaya, it was found that 70% of 10 students had low levels of knowledge and 90% of 10 students showed poor attitudes towards people living with HIV/AIDS. Therefore, effective health education efforts are needed, one of which is through leaflets and videos. This study used a quantitative method with a quasi-experimental design of the Two-Group Pretest-Posttest Design type. The sample consisted of 30 eleventh-grade students divided into two groups, with 15 students receiving education through leaflets and 15 students through videos. The Paired Sample T-Test was used because the data was normally distributed. The results of the study on the leaflet media group showed an increase in knowledge with a mean = -4.667 and a p-value = 0.000, while the increase in attitude had a mean = -6.600 and a p-value = 0.000. A p-value <0.05 indicates that there was a significant difference between the values before and after the educational intervention was given. It can be concluded that leaflets are effective in increasing students' knowledge and attitudes about HIV/AIDS. Meanwhile, in the video education group, the mean increase in knowledge was -3.867 with a p-value of 0.000, and the mean increase in attitude was -4.000 with a p-value of 0.000. This also indicates that there is a significant difference in knowledge and attitudes before and after the educational intervention. It can be concluded that both leaflets and videos are effective in increasing students' knowledge about HIV/AIDS. This study demonstrates that health education interventions using leaflet and video media can effectively improve knowledge and attitudes toward HIV/AIDS. The leaflet-based intervention showed greater effectiveness in shaping positive attitudes, likely due to repeated exposure and deeper comprehension of written information. These findings support the integration of printed educational media as a complementary strategy in HIV/AIDS prevention programs.